188k views
5 votes
14. question in attachment

14. question in attachment-example-1

1 Answer

4 votes


answer \\ = 2x - 2 \\ solution \\ given \: data = x + 1 </em></strong><strong><em>,</em></strong><strong><em>\: 3x - 2 </em></strong><strong><em>,</em></strong><strong><em>\: 2x - 5 \\ n(total \: number \: of \: items) = 3 \\ we \: have \: to \: find \: mean \: of \: the \: given \\ data \\ mean = (x + 1 + 3x - 2 + 2x - 5)/(3) \\ \: \: \: \: \: \: \: = (x + 2x + 3x + 1 - 2 - 5)/(3) \\ \: \: \: \: \: \: = (6x - 1 - 5)/(3) \\ \: \: \: \: = (6x - 6)/(3) \\ \: \: \: \: = 2x - 2 \\ hope \: it \: helps

User Abhi Adr
by
5.9k points